Quality and post-harvest life of Mexican lemon fruits from trees with symptoms of HLB and asymptomatic - Saucedo-Veloz, Crescenciano; Hernández-Rivera, Aideé; Arellano-Ostoa, Gregorio; Robles-Gonzales, Manuel Marciano; Jaén-Contrearas, David; Contreras-Oliva, Adriana (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico, the presence of Huanglongbing (HLB) in the producing areas of Mexican lemon, has been manifested in a reduction in production that, in the case of the Colima production area, has been estimated at 66.8% in the last 10 years. The effect of the disease on the quality of the fruits has been little studied, the reduction in size being reported. The objective was to evaluate the organoleptic and nutritive quality, related to the postharvest behavior of Mexican lemon fruits from trees with HLB and asymptomatic. Fruits were harvested from trees with and without symptoms of HLB from the INIFAP Fruit Experimental Field, Tecoman Colima, Mexico. Four treatments were established considering the origin of the fruits (trees with symptoms of HLB and asymptomatic) and two temperatures (environment: 22 ±2 ºC per 4 and 8 days, refrigeration: 9 ±1 ºC per 2 weeks plus 4 and 8 days to the environment). After each period, the following variables were evaluated: SST, titratable acidity, technological index, ascorbic acid (vitamin C), weight loss, color index and damages by cold. Regarding these variables, no significant differences were observed, at the time of harvest, between fruits of trees with symptoms of HLB and asymptomatic. The post-harvest behavior was similar during the two storage conditions and no differences in the variables were observed; however, the losses of weight, ascorbic acid and green color were greater in fruits from trees with HLB, in addition to having a higher incidence of cold damage. It is concluded that the quality, evaluated by the mentioned variables, of the fruits from trees with symptoms of HLB and asymptomatic is not significantly affected, except that the fruits harvested from trees with HLB are more sensitive to cold damage.